Xanthogranulomatous pancreatitis combined with multifocal necrosis: A case report and literature review. Issue 6 (27th December 2020) - Tang, Xuemei; Lu, Wenming
Abstract : Xanthogranulomatous inflammation is rare and occurs in several viscera in the body, such as the kidney, gallbladder, bone, and stomach. The pathogenesis of Xanthogranulomatous pancreatitis (XGP) is not well understood, and the disease is characterized by lipid-laden histiocytes deposited at various sites in the organs. XGP associated with multifocal necrosis is extremely rare. In this report, we described a case of XGP associated with multifocal necrosis and included a review of the literature.